TRADITIONAL AND INDIGENOUS PRACTICES OF SOME MEDICINAL PLANTS AS IMMUNITY BOOSTERS BY FOLKLORE OF MANDI DISTRICT, HIMACHAL PRADESH - Sharma Ritu; Goraya G.S; Seth M.K (International Journal of Ayurveda and Pharma Research, 2020)
Himachal Pradesh being a hilly State is one of the top repositories of various herbal plants of medicinal aspects. District Mandi, popular as Varanasi of Hills, is one of the twelve districts, with great variations in elevation which provide a suitable habitat for the rich biodiversity of flora and fauna. The present paper aimed to document indigenous uses of some therapeutically significant plants which have been utilized by folklore to improve their immunity and to cure immunity-related diseases like cough, cold, and allergies. Indeed, even today when the Corona pandemic has influenced the whole world gravely, provincial fables of the State have kept themselves safe and have indicated their confidence on these plant assets which are being utilized by their predecessors for ages. Herein 21 species belonging to 17 families used as immunity boosters are compiled (8 herbs, 6 shrubs, 6 trees, 1 climber) used by folklore to enhance their immunity. Documentation of traditional knowledge is the need of the hour as it the base of the Naturopathy and Ayurveda. The documentation of the traditional medicinal knowledge will give another point of view to herbal drug researchers for extending and improving the utilization of botanical drugs and their therapeutic applications. Plant-based natural products offer an infinite source of compounds to help to design the pharmacologically important molecular products and novel drug discovery as well.